2021
DOI: 10.3389/fpsyt.2021.735615
|View full text |Cite|
|
Sign up to set email alerts
|

Paradoxes in Borderline Emotional Dysregulation in Adolescence: Influence of Parenting, Stressful Life Events, and Attachment

Abstract: Introduction: Borderline personality disorder (BPD) in adolescents is characterized by emotional dysregulation, insecure attachment, a history of stressful life events (SLEs) as well as dysfunctional parent–child interactions. The respective contribution of each of these factors on BPD affective symptoms is not yet clear. The purpose of this study is to assess the distinct impact of parental adversity and SLEs on BPD affective symptoms and the role of attachment and alexithymia in such emotional processes.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Early adversity in borderline pathology has a significant impact on neural and cognitive functioning associated with the stress axis through epigenetic mechanisms ( 25 27 ). It also disrupts attachment patterns, which in turn contribute to the development and perpetuation of borderline symptoms ( 2 , 28 ). Research has shown that severe childhood maltreatment is prevalent among adult patients with BPD, and similar findings have been observed in adolescents ( 29 ).…”
Section: Local Therapeutic Containmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Early adversity in borderline pathology has a significant impact on neural and cognitive functioning associated with the stress axis through epigenetic mechanisms ( 25 27 ). It also disrupts attachment patterns, which in turn contribute to the development and perpetuation of borderline symptoms ( 2 , 28 ). Research has shown that severe childhood maltreatment is prevalent among adult patients with BPD, and similar findings have been observed in adolescents ( 29 ).…”
Section: Local Therapeutic Containmentmentioning
confidence: 99%
“…These situations may include the fear of separation, relationship difficulties, or the feeling that their needs are not being met. Patients tend to anticipate negative events and perceive the world as threatening, which can lead them to generalize their experiences and interpret even minor situations as highly significant ( 28 ). During the interview, a thorough analysis of these relational situations allows the patient's conscious experiences to be compared with their unexpressed emotional and bodily reactions.…”
Section: Individual Therapeutic Containmentmentioning
confidence: 99%
“…The manifestations of this dysregulation include risky behaviors (alcohol and substance use disorders, risky sexual behaviors), disruptive behaviors (damaging objects or hetero-aggressive behaviors) and self-harm with or without suicidal intent. A rising number of adolescents with these characteristics are hospitalized in mental health services, with prolonged hospital stays, decreasing quality of life and higher healthcare costs (7,8).…”
Section: Introductionmentioning
confidence: 99%